2015
DOI: 10.6061/clinics/2015(06)03
|View full text |Cite
|
Sign up to set email alerts
|

Septic pulmonary embolism caused by a Klebsiella pneumoniae liver abscess: clinical characteristics, imaging findings, and clinical courses

Abstract: OBJECTIVES:Septic pulmonary embolism caused by a Klebsiella (K.) pneumoniae liver abscess is rare but can cause considerable morbidity and mortality. However, clinical information regarding this condition is limited. This study was conducted to elucidate the full disease spectrum to improve its diagnosis and treatment.METHOD:We reviewed the clinical characteristics, imaging findings, and clinical courses of 14 patients diagnosed with septic pulmonary embolism caused by a K. pneumoniae liver abscess over a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 35 publications
2
31
1
2
Order By: Relevance
“…In addition, Nguyen et al reported CT findings, including consolidations, multiple nodules and GGA, from nine patients with community-acquired MRSA pneumonia 23 . SPE can present as consolidations, multiple nodules with cavities and GGA in CT images 6 , all of which are present in pneumonia, thus making distinguishing SPE from pneumonia difficult. In the present study, CT examinations showed multiple different sizes of nodules with cavities, as shown in Figure 2 , which is suggestive of SPE instead of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Nguyen et al reported CT findings, including consolidations, multiple nodules and GGA, from nine patients with community-acquired MRSA pneumonia 23 . SPE can present as consolidations, multiple nodules with cavities and GGA in CT images 6 , all of which are present in pneumonia, thus making distinguishing SPE from pneumonia difficult. In the present study, CT examinations showed multiple different sizes of nodules with cavities, as shown in Figure 2 , which is suggestive of SPE instead of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with SPE are diagnosed on the basis of CT findings and the presence of a primary source of infection 2 4 because histopathological confirmation is typically unfeasible in clinical practice 2 . The clinical presentations of SPE range from insidious illness with mild respiratory symptoms to respiratory failure and septic shock 6 . Despite its life-threatening nature, data on patients with SPE who require critical care have not been well reported.…”
Section: Introductionmentioning
confidence: 99%
“…The most common sources are liver abscess (50%) and pneumonia (25%). Acute kidney injury, disseminated intravascular coagulation and lung abscesses are common in non-survivors [31,32].…”
Section: Pulmonary Thromboembolismmentioning
confidence: 99%
“…1,2 The patients may present with insidious respiratory illness with fever and breathlessness which may also deteriorate leading to acute respiratory failure, septic shock, multiorgan dysfunction syndrome and systemic inflammatory response syndrome. 3 Symptoms cover the entire spectrum from asymptomatic patients to sudden death. 1 The source of infection is of wide range and most common source of septic embolism in lung is being infective foci in right heart (eg.…”
Section: Introductionmentioning
confidence: 99%